PERANCANGAN STRATEGI MITIGASI RISIKO DAN KEY RISK INDICATORS PADA BLOOD SUPPLY CHAIN PMI KABUPATEN GUNUNGKIDUL - Sunyoto, Danang; Kalijaga, Magister Alfatah (Jurnal Ilmiah Teknik Industri, 2023)
The concept of blood supply chain is distribute blood products safely, cheaply, and accessible to patients. There are four main activities in the blood supply chain, namely blood collection, blood processing, laboratory testing, and storage and distribution of blood products. The current development of PMI Gunungkidul Regency in carrying out its duties is still hampered by several things caused by risks, one of which is supply and demand uncertainty. In 2021, the blood supply at PMI will still experience a crisis of decreasing by 20%-30%, while the demand for blood from hospitals continues to exist and fluctuates. Based on the results of House of Risk Phase 1, there are 10 dominant risks that affect the blood supply chain. The results of the House of Risk Phase 2 resulted in preventative action to handle the 10 dominant risks. Apart from that, the results of the key risk indicators (KRI) are used as an early warning system for PMI Gunungkidul Regency. Implementation of preventive actions that have been designed and implemented key risk indicators, namely the number of blood bag supplies per month with a limit value of 79 blood bags and 399 blood bags.